PARTISIPASI MASYARAKAT SEBAGAI PERANGKAT HISTORIC URBAN LANDSCAPE DALAM PENGELOLAAN KAWASAN SUMBU FILOSOFI DI DAERAH ISTIMEWA YOGYAKARTA - Fadlliyah, Laily; Setiawan, Bakti (Jurnal Perencanaan dan Pengembangan Kebijakan, 2023)
Historic Urban Landscape is a historic city management approach that is considered more comprehensive in balancing between social and economic development and cultural heritage conservation. UNESCO adopted the Recommendation on The Historic Urban Landscape on 10 November 2011 at the UNESCO General Assembly. As an approach that can be adopted by various countries, this approach recommends four main tools, namely civic engagement, knowledge and planning, regulatory system, and financial tools. This research aims to identify civic engagement tools in the management of the historic city area called Kawasan Sumbu Filosofi in the Special Region of Yogyakarta. This research uses a qualitative approach with a type of case study research and is descriptive in nature. Data collection techniques were carried out through interviews, observation, and literature studies. This research reveals that civic engagement in the management of the Kawasan Sumbu Filosofi in the voice area has been granted and guaranteed through various regulations. In terms of access, the government has provided a space for discussion, but the information the government provides still predominates in this forum. Concerning the aspect of control, community control over the surrounding environment has not been built. In general, the quality of community participation must continue to be encouraged to realize sustainable urban development and preservation.